Winter survival of the unicellular green alga Micrasterias denticulata: insights from field monitoring and simulation experiments - Philip Steiner; Othmar Buchner; Ancuela Andosch; Andreas Holzinger; Ursula Lütz-Meindl; Gilbert Neuner (Protoplasma, 2021)
Peat bog pools around Tamsweg (Lungau, Austria) are typical habitats of the unicellular green alga Micrasterias denticulata . By measurement of water temperature and irradiation throughout a 1-year period (2018/2019), it was intended to assess the natural environmental strain in winter. Freezing resistance of Micrasterias cells and their ability to frost harden and become tolerant to ice encasement were determined after natural hardening and exposure to a cold acclimation treatment that simulated the natural temperature decrease in autumn. Transmission electron microscopy (TEM) was performed in laboratory-cultivated cells, after artificial cold acclimation treatment and in cells collected from field. Throughout winter, the peat bog pools inhabited by Micrasterias remained unfrozen. Despite air temperature minima down to −17.3 °C, the water temperature was mostly close to +0.8 °C. The alga was unable to frost harden, and upon ice encasement, the cells showed successive frost damage. Despite an unchanged freezing stress tolerance, significant ultrastructural changes were observed in field-sampled cells and in response to the artificial cold acclimation treatment: organelles such as the endoplasmic reticulum and thylakoids of the chloroplast showed distinct membrane bloating. Still, in the field samples, the Golgi apparatus appeared in an impeccable condition, and multivesicular bodies were less frequently observed suggesting a lower overall stress strain. The observed ultrastructural changes in winter and after cold acclimation are interpreted as cytological adjustments to winter or a resting state but are not related to frost hardening as Micrasterias cells were unable to improve their freezing stress tolerance.

The conjugating green alga Zygnema sp. (Zygnematophyceae) from the Arctic shows high frost tolerance in mature cells (pre-akinetes) - Kateřina Trumhová; Andreas Holzinger; Sabrina Obwegeser; Gilbert Neuner; Martina Pichrtová (Protoplasma, 2019)

Leaf anatomy of two reciprocally non-monophyletic mountain plants (Heliosperma spp.): does heritable adaptation to divergent growing sites accompany the onset of speciation? - Clara Bertel; Peter Schönswetter; Božo Frajman; Andreas Holzinger; Gilbert Neuner (Protoplasma, 2017)

Is sexual reproduction of high-mountain plants endangered by heat? - Ursula Ladinig; Manuel Pramsohler; Ines Bauer; Sonja Zimmermann; Gilbert Neuner; Johanna Wagner (Oecologia, 2015)

Heat tolerance of early developmental stages of glacier foreland species in the growth chamber and in the field - Silvia Marcante; Brigitta Erschbamer; Othmar Buchner; Gilbert Neuner (Plant Ecology, 2014)

How endangered is sexual reproduction of high-mountain plants by summer frosts? Frost resistance, frequency of frost events and risk assessment - Ursula Ladinig; Jürgen Hacker; Gilbert Neuner; Johanna Wagner (Oecologia, 2013)

Correspondence of seed traits with niche position in glacier foreland succession - Erich Schwienbacher; Jose Antonio Navarro-Cano; Gilbert Neuner; Brigitta Erschbamer (Plant Ecology, 2012)

Freezing cytorrhysis and critical temperature thresholds for photosystem II in the peat moss Sphagnum capillifolium - Othmar Buchner; Gilbert Neuner (Protoplasma, 2010)

Leaf wettability decreases along an extreme altitudinal gradient - Biva Aryal; Gilbert Neuner (Oecologia, 2010)